PENGARUH PENGGUNAAN MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS VA - Astrid Putri Najira. S; Aco Karumpa, Andi Syamsul Alam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the Inside Outside Circle (IOC) learning model on students’ learning outcomes in Indonesian speaking skills. The background of this research stems from the low learning outcomes of class VA students at SD Inpres Minasaupa 1, particularly in speaking skills. The method used is an experimental method with a one-group pretest-posttest design. The population and sample consisted of all 21 students of class VA. Data collection techniques involved oral tests to assess speaking skills, including pronunciation, grammar, vocabulary, and fluency. The Inside Outside Circle model is part of a cooperative learning approach that encourages students to share information with different partners in a structured rotation. This model emphasizes active student participation, especially in verbal communication activities. The results showed a significant improvement in students' learning outcomes after implementing the IOC model. The average pretest score was 57.86, while the posttest score increased to 70.71. A paired sample t-test yielded a significance value of < 0.001, indicating a statistically significant difference between pretest and posttest scores. Therefore, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. In conclusion, the use of the Inside Outside Circle (IOC) learning model has a positive and significant effect on improving students' speaking skills in Indonesian language learning. This research suggests that teachers can apply the Inside Outside Circle (IOC) model as an effective alternative method to enhance learning outcomes, especially speaking skills, at the elementary school level.